Implementation of Sharia Business Ethics in Business Feasibility: A Case Study of Tette Chips in Pamekasan - Syofiana Mailinda; Abdur Rohman (Al-Arfa: Journal of Sharia, Islamic Economics and Law, 2025)
This study examines in depth the application of Sharia business ethics principles in the feasibility study of the Kripik Tette business in Branta Tinggi Village, Pamekasan Regency. As a local small and medium-sized enterprise (SME), Kripik Tette not only has significant economic potential but also holds strong cultural values in Madurese society. Sharia business ethics, rooted in universal values such as honesty, justice, trustworthiness, and social responsibility, serve as a crucial foundation for building a business that does not solely pursue profit but also prioritizes economic, social, and spiritual sustainability. The research method employed is qualitative, utilizing direct observation of business activities. The research findings indicate that Sharia business ethics principles have been effectively applied across various operational aspects of the business, including fair labor relations, the use of safe and high-quality raw materials, and community involvement in the production process. The implementation of these ethics has significantly enhanced consumer trust, empowered local communities, supported the well-being of cassava farmers, and fostered a healthy and harmonious business ecosystem. However, this study also identified challenges in maintaining the consistency of ethical practices, particularly related to market fluctuations and the understanding of Sharia ethics among other business actors. Collaborative and sustained efforts are needed between business actors, the community, the government, and academics to strengthen the understanding and implementation of Sharia values in the business world, in order to achieve inclusive and sustainable economic growth.